(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The morphometric observations were made on total length, standard length, pre-caudal length, head length, eye diameter and depth of body at pectoral fin base of estuarine catfish M. gulio. Males and females showed homogeneity in characters. A linear relationship was found between total length and morphometric characters. Regression of length and weight did not deviate significantly from cube law indicating isometric growth. The fish exhibited sexual dimorphism. Keywords: Morphometric characters; Estuarine catfish; Mystus gulio DOI: 10.3329/jbau.v6i2.4833 J. Bangladesh Agril. Univ. 6(2): 349-353, 2008